Knowledge, attitudes, and practices of Anopheles mosquito control through insecticide treated nets and community-based health programs to prevent malaria in East Sumba Island, Indonesia. - John T Bandzuh; Kacey C Ernst; Jayleen K L Gunn; Salmon Pandarangga; Linda Rambu Kuba Yowi; Sarah Hobgen; Kerry R Cavanaugh; Rambu Yetti Kalaway; Norlina Rambu Jola Kalunga; Maklon Felipus Killa; Umbu Ho Ara; Christopher K Uejio; et al. (Public Library of Science (PLoS), 2022)
With an estimated 241 million human cases and 627,000 deaths in 2020, malaria remains a significant and ongoing global health challenge. This study employs a qualitative approach to investigate knowledge, attitudes, and practices surrounding mosquito control and prevention methods in East Sumba Regency, Indonesia. While malaria is under control in much of Indonesia, transmission in Sumba Island remains high, with incidence as high as 500 per 1000 population in some areas. A qualitative study was undertaken to explore use of insecticide treated nets, (ITNs), traditional Sumbanese mosquito control methods, and the role of women, integrated health service posts, (posyandu) and community-based health workers (kaders) in combatting malaria and controlling mosquitoes. Focus group discussions (n = 7) were conducted in East Sumba Island stratified by urban/rural location and level of malaria transmission. Key informant interviews (n = 14) were conducted with religious leaders, health workers, and women's group leaders. Results indicate that environmental conditions, such as high temperatures, were common deterrents to regular ITN use. Furthermore, our results suggest that community embedded health workers, kaders, and health service posts, posyandu, play an important role in information dissemination related to mosquitoes and mosquito-borne diseases as well as the distribution and use of ITNs in East Sumba Island. The role of the posyandu and kaders could be expanded to improve malaria prevention by integration with educational campaigns, aiding ITN distributions, and malaria diagnosis and treatment. This study is the first to examine mosquito-borne disease-related knowledge, attitudes, and practices in East Sumba Island, Indonesia. Results could improve mosquito control and malaria prevention by providing insights into local knowledge of Anopheles mosquitoes and malaria as well. Tailoring mosquito control and malaria prevention strategies around local knowledge and perceptions is likely to be more acceptable and sustainable.